Chemical Constituents, Antimicrobial and Antibiofilm Activity of Lophocereus schottii Against Uropathogenic Escherichia coli - Roberto, Tapia-Rodríguez Melvin; Max, Vidal-Gutiérrez; Alejandra, González-Ortiz; Enrique, Robles-Zepeda Ramón; Wagner, Vilegas [UNESP]; Fernando, Ayala-Zavala Jesús; Norma, Velázquez-Guadarrama; Heriberto, Torres-Moreno; César, López-Romero Julio (Taylor & Francis, 2022)
The objective of the present study was to determine the chemical profile, and the antimicrobial and antibiofilm effect of the Lophocereus schottii extract against uropathogenic Escherichia coli. A methanolic extract of L. schottii was analyzed by mass spectrometry (ESI-IT-MSn and APCI-IT-MSn) to determine the profile of bioactive compounds. The antimicrobial potential was assayed by the microdilution broth method. The effect of the extract on motility was also determined. Quorum sensing systems were evaluated using a biosensor with Chromobacterium violaceum. The prevention of biofilm formation and biofilm remotion were analyzed by the crystal violet method. The chemical analysis allows to identify 8 phenolic compounds, 2 alkaloids and 1 triterpene, most of these reported for the first time to this plant. L. schottii extract showed inhibitory and bactericidal activity against uropathogenic E. coli (MIC= 6.5 mg/mL and CMB= 13 mg/mL). In addition, the effect of L. schottii on motility was observed, since the concentration of 6.5 mg/mL reduced this process by 60%. With regard to the inhibition of the Quorum sensing system, L. schottii (6.5 mg/mL) reduce the production of violacein in 45%. The same concentration of the extract (6.5 mg/mL) resulted the most effective to prevent biofilm formation in 65%. Regarding the biofilm remotion the higher tested concentration (3 MIC) was the most effective, removing 84% of biomass. The results showed that L. schottii has a variety of bioactive compounds and antimicrobial and antibiofilm potential against uropathogenic E. coli.
Keywords: antibiofilm; antimicrobial; bioactive compounds; Uropathogenic Escherichia coli